Learning assessment model in biology education during the COVID-19 pandemic - Yuni Pantiwati; Tasya Novian Indah Sari; Mia Nurkanti (JPBI (Jurnal Pendidikan Biologi Indonesia), 2022)
The COVID-19 Pandemic has resulted the change in every sector of life. Education institutions transform their learning methods from face-to-face learning to online-based distance learning to keep the learning process running during the pandemic era. The purpose of this study is to obtain the description and analysis results regarding learning profile and evaluation system used in the lecture at Biology Education Study Program during the Pandemic. This survey study was conducted in August 2020 until August 2021, even semester of 2019/2020, odd semester of 2019/2020, even semester of 2020/2021, and odd semester of 2021/2022. The population of this study was the students of Biology Education of UMM and the students of private universities in Malang City. Purposive sampling was employed for sample selection. The instruments used were survey and questionnaire forms. The data was analyzed descriptively and quantitatively. The results of the study show that online learning is apparently not optimal in Biology Education and other private universities in Malang due to limitations in discussions, assignments, and assessments. Therefore, it is necessary to conduct training session, planning, and implementation of innovative online learning to optimize learning process. To make the learning process more accurate and effective, evaluations are also needed.